Fragmentation and Vertical Fiscal Imbalances Lessons from Moldova - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2014)
Using a novel municipality-level panel dataset, this paper investigates the empirical characteristics of vertical fiscal imbalances (VFIs) in Moldova over the period 2005-13. The results show that the extent of variation in VFIs across 898 municipalities can be explained by the level of per capita income, fiscal capacity, and demographic characteristics, as well as the central government's fiscal behavior that reflects fiscal constraints and policy preferences at the national level. Political affiliation does not appear to be a significant factor, and the results are inconclusive in terms of direction. While some model specifications show larger VFIs when the mayor of a municipality belongs to the same party ruling the central government, other models suggest better coordination and thus lower VFIs. Altogether, these findings underscore the need for well-coordinated reforms to create economies of scale, enhance revenue collection, and improve the composition of spending at the subnational level.